Automatic dental age estimation in adolescents via oral panoramic imaging - Li, Ze; Xiao, Ning; Nan, Xiaoru; Chen, Kejian; Zhao, Yingjiao; Wang, Shaobo; Guo, Xiangjie; Gao, Cairong (Frontiers in Dental Medicine, 2025)
ObjectIn forensic dentistry, dental age estimation assists experts in determining the age of victims or suspects, which is vital for legal responsibility and sentencing. The traditional Demirjian method assesses the development of seven mandibular teeth in pediatric dentistry, but it is time-consuming and relies heavily on subjective judgment.MethodsThis study constructed a largescale panoramic dental image dataset and applied various convolutional neural network (CNN) models for automated age estimation.ResultsModel performance was evaluated using loss curves, residual histograms, and normal PP plots. Age prediction models were built separately for the total, female, and male samples. The best models yielded mean absolute errors of 1.24, 1.28, and 1.15 years, respectively.DiscussionThese findings confirm the effectiveness of deep learning models in dental age estimation, particularly among northern Chinese adolescents.